Analysis of the competitiveness indicators of strawberry exports Mexican - Ramírez Padrón, Laura Cecilia; Cauich, Ignacio Caamal; Fernández, Verna Gricel Pat; Luis, David Martínez; Fernández, Alberto Pérez (Revista Mexicana de Ciencias Agrícolas, 2020)
The main strawberry producing countries are China, the United States of America, Mexico, Turkey and Egypt, which together contribute more than seventy percent of the total volume of strawberry production in the world and, on the other hand, the main exporting countries are Spain, the United States of America, Mexico, the Netherlands and Belgium, highlighting Mexico as the third largest strawberry producer and exporter in the world. The objective of the work is to analyze the competitiveness of the exports of the Mexican strawberry in the world exporting market, with the calculation of the export indexes, relative advantage of exports and revealed comparative advantage, with statistical information of the production variables, export and import, taken from the FAS-USDA and FAOSTAT databases. The export indices obtained, greater than zero, relative advantage of exports, greater than one and revealed comparative advantage, greater than one, reflect that the production of Mexican strawberry has an export specialization and the exports of Mexican strawberry are competitive in the export market. Likewise, the positive calculated indexes for the main exporting countries were higher for Spain, followed by Mexico and finally by the United States of America, reflecting export specialization and competitiveness of differentiated exports.